Policy Synergy Model in Earthquake Disaster Management in Cianjur Regency - Iwan Satibi (International Journal of Science and Society, 2023)
This research is based on a phenomenon that indicates the ineffectiveness of policy synergy in dealing with the impact of the earthquake disaster in Cianjur Regency. This phenomenon can be observed from several indications, including the lack of fully effective communication patterns among stakeholders involved in disaster management. Apart from that, it was detected that there were still differences in perceptions from some stakeholders in dealing with technical matters, so that the provision of assistance tended to be uneven. There were delays in evacuating and relocating those affected by the disaster. Through desk study methods and approaches, research results were found, including; To synergize earthquake disaster management policies in Cianjur Regency, clear parameters are needed, so that all stakeholders can carry out their duties in accordance with their roles and functions. The parameters referred to include, among other things, the existence of similarities in perception, potential resources, communication patterns, attitudes of policy actors, and organizational structure. Similarity of perception among stakeholders in disaster management will be effective if a common perception is established regarding objectives, content, programs and implementation. To translate disaster management policies, potential resources are needed which include human resource capabilities, budget, facilities and technology. Meanwhile, to facilitate communication in disaster management, clarity, speed and accuracy of communication patterns are needed, then there needs to be socialization and cooperation as well as completeness of information. To build the integrity and trust of the public in the authorities in dealing with the impacts of disasters requires the attitude of policy actors who have responsiveness, consistency and commitment. Meanwhile, to help facilitate the process of dealing with the impact of disasters, an organizational structure is needed which includes; aspects of division of authority, support from all stakeholders and clarity of procedures (SOP).